Lubricant, lubricating composition and sliding machine

A lubricant with a novel structure forms a stable adsorption film on sliding surfaces, enhancing wear resistance and reducing friction, addressing the lack of effective film formation in existing compositions and offering environmental benefits.

JP2024176288APending Publication Date: 2024-12-19KK TOYOTA CHUO KENKYUSHO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023094743
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing lubricating compositions do not effectively address the formation of an adsorption film on sliding surfaces, which is crucial for improving sliding characteristics such as wear resistance and reducing friction.

Method used

A lubricant with a new structure featuring two alkyl esters bonded to a hydrocarbon amine main chain, forming a stable adsorption film on sliding surfaces, thereby enhancing lubricity and reducing viscosity.

Benefits of technology

The lubricant forms a strong adsorption film quickly, providing stable sliding properties with improved wear resistance and low friction, while being environmentally friendly and preventing mechanical system clogging and catalyst poisoning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176288000001_ABST
    Figure 2024176288000001_ABST
Patent Text Reader

Abstract

To provide a lubricant capable of forming a stable adsorbed film on a sliding surface and stabilizing sliding characteristics (e.g., ensuring wear resistance, etc.).SOLUTION: The present invention provides a lubricant having the following chemical structural formula (R: a hydrocarbon group having 8 to 24 carbon atoms, and x and y: integers from 1 to 6).SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lubricant and the like. [Background technology]

[0002] Machines with sliding parts are designed to have a longer life and reduce losses (improved efficiency) by reducing wear and friction. Such sliding characteristics are greatly influenced by the lubricant (including not only additives but also compositions of additives and base oils (lubricating oils)) supplied to (present in) the sliding parts. For this reason, many proposals have been made regarding lubricants, and for example, the following patent documents contain related descriptions. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2002-338983 [Patent Document 2] Patent Publication No. 2022-24803 Summary of the Invention [Problem to be solved by the invention]

[0004] Patent Document 1 proposes a lubricating composition having excellent rust-preventing performance. Patent Document 2 proposes a lubricating composition for diesel engines having a desired viscosity.

[0005] These patent documents contain no description or suggestion relating to the adsorptivity of a lubricating composition on a sliding surface or the film formed on the sliding surface.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a new lubricant or the like that can improve sliding characteristics. [Means for solving the problem]

[0007] As a result of intensive research into solving this problem, the inventors have developed a lubricant with a new structure that has excellent adhesion to sliding surfaces. By expanding on this result, the present invention, which will be described below, has been completed.

[0008] Lubricants (1) The present invention is a lubricant represented by the following chemical structural formula:

[0009] [ka] (R: a hydrocarbon group having 8 to 24 carbon atoms, x and y: integers of 1 to 6)

[0010] (2) When the lubricant of the present invention is used in sliding machines, an adsorbed film is stably formed on the sliding surface, improving the sliding characteristics.

[0011] The reason and mechanism by which the lubricant of the present invention exhibits such excellent effects is not entirely clear, but at present, it is believed to be as follows. The lubricant of the present invention has the chemical structural formula (1), Two alkyl esters (functional groups) are bonded to the ends of the hydrocarbon amine (main skeleton, main chain). These functional groups become adsorbing groups that are more stably adsorbed to the surface of a substrate (e.g., steel) than conventionally. When the lubricant of the present invention (or a composition thereof) is supplied to the sliding part (between sliding surfaces) of a sliding machine, a strong adsorbing film is quickly formed (e.g., immediately after the start of operation of the sliding machine) on at least one of the sliding surfaces, and sliding characteristics (wear resistance, low friction, etc.) can be stably expressed. According to the lubricant of the present invention, for example, it is possible to sufficiently ensure lubricity and oil film thickness while achieving trace amount lubrication and low viscosity of the lubricating oil.

[0012] The lubricant of the present invention is an organic lubricant that does not contain non-organic components such as metal elements, phosphorus, sulfur, etc. Organic lubricants have a small environmental impact, are biodegradable, and are also effective in preventing clogging of mechanical systems and poisoning of exhaust purification catalysts in internal combustion engines.

[0013] 《Lubricating composition》 The present invention can also be understood as a lubricating composition containing the above-mentioned lubricant. The lubricating composition may be, for example, a liquid phase (mixture) containing the lubricant, or a solid phase (composite) in which the lubricant is dispersed. Representative examples of the lubricating composition include lubricating oil (liquid phase) in which the lubricant is added to a base oil, and grease (solid phase) in which the lubricant is dispersed in a base oil.

[0014] Sliding Machine The present invention can also be understood as a sliding machine having a sliding surface to which the above-mentioned lubricant is supplied. Typical examples of sliding machines include engines and transmissions. The lubricant is supplied to the sliding surface as, for example, lubricating oil. Typical examples of lubricating oil include engine oil, transmission oil (including automatic transmission fluid (ATF)), gear oil, etc.

[0015] "others" (1) The hydrocarbon group R in this specification may be a saturated or unsaturated group, and may be a straight-chain or branched group.

[0016] (2) Unless otherwise specified, "α to β" in this specification includes a lower limit value α and an upper limit value β. Any numerical value included in the various numerical values ​​or numerical ranges described in this specification may be used as a new lower limit or upper limit value to create a new range such as "a to b". Furthermore, unless otherwise specified, "α to β ppm" in this specification means α ppm to β ppm. The same applies to other unit systems. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is an explanatory diagram showing an example of synthesis of a lubricant. [Diagram 2] 1 is a spectrum showing an example of analysis of a lubricant by 1H-NMR. [Diagram 3] FIG. 1 is a schematic diagram of a cross-pin wear test. [Figure 4] 1 shows a photograph illustrating wear scars obtained by a wear test and a bar graph comparing wear scar widths. [Diagram 5] 1 shows the molecular structure of the additive used in the molecular calculation. [Figure 6A]This is a phase diagram showing the distribution (adsorption onto the substrate surface) of additive molecules (sample 1) obtained by the analysis. [Figure 6B] This is a phase diagram showing the distribution (adsorption onto the substrate surface) of additive molecules (sample 2) obtained by the analysis. [Figure 6C] This is a phase diagram showing the distribution (adsorption onto the substrate surface) of additive molecules (sample C1) obtained by the analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The components of the present invention may include one or more components selected from the present specification. The contents described in this specification may apply not only to lubricants and lubricating compositions, but also to sliding machines and sliding members. Components related to a manufacturing method may also be components related to an object. Which embodiment is best depends on the target, required performance, etc.

[0019] Lubricants The lubricant is composed of a molecule represented by the chemical structural formula (1). R constituting the main chain of this molecule is a hydrocarbon group having 8 to 24, 12 to 22, or even 16 to 20 carbon atoms. The hydrocarbon group may be a saturated hydrocarbon group (alkyl group) or an unsaturated hydrocarbon group (alkene group, alkane group). Examples of the hydrocarbon group constituting the main chain include alkyl groups such as oleyl, 2-ethylhexyl, n-octyl, isooctyl, nonyl, decyl, undecyl, dodecyl, lauryl, tridecyl, pentadecyl, hexadecyl, palmitoleyl, heptadecyl, octadecyl, stearyl, linoleyl, nonadecyl, tetradecyl, and arachidyl, or unsaturated alkyl groups (alkenyl groups).

[0020] The two functional groups (alkyl esters) in chemical structure (1) may have the same or different numbers of carbon atoms (x, y) in the alkyl groups. Usually, making the numbers of carbon atoms the same (x=y) makes it easier to synthesize the lubricant.

[0021] Molecular example shown in chemical structure (1) (R=C 18 H35 ) can be obtained, for example, by proton nuclear magnetic resonance spectroscopy ( 1 When analyzed by H-NMR, the chemical shift values ​​of the spectrum showing Ha, Hb, and Hc in the following chemical structural formula (2) can be around 3.7 ppm, around 2.7 ppm, and around 5.4 ppm, respectively.

[0022] [ka]

[0023] 《Organic film》 An organic film derived from the lubricant may be formed on the sliding surface to which the lubricant is supplied. This organic film may be formed only from the molecules shown in chemical structural formula (1), or may be generated by the reaction of these molecules with surrounding molecules (e.g., the constituent molecules of the base oil). Although the mechanism of its formation is unclear, it is thought that two functional groups (alkyl esters) in the lubricant molecules are firmly and quickly adsorbed to the sliding surface (substrate surface), forming an organic film with excellent sliding properties.

[0024] The presence or absence of an organic film can be determined, for example, based on a profile (position and magnitude of spectrum) obtained by performing positive ion spectrum analysis on a sliding surface in contact with a lubricant using time-of-flight secondary ion mass spectrometry (TOF-SIMS). The detection sensitivity (peak intensity / peak area) by TOF-SIMS is likely to vary from sample to sample. By using the intensity (reference area) of a specific peak obtained for each sample as a reference and evaluating the intensity (area) of other peaks (i.e., normalizing with the reference area), it is also possible to quantitatively analyze the organic film.

[0025] <Lubricant composition / sliding machine> Examples of lubricating compositions include engine oils and transmission oils (including ATFs) in which a lubricant is added to a base oil. Examples of sliding machines include engines and transmissions. The lubricant of the present invention can quickly form an organic adsorption film on the sliding surface, so it is also suitable for low-viscosity lubricating compositions and sliding machines operated in low temperature ranges (e.g., transmissions, internal combustion engines dedicated to hybrid vehicles, etc.).

[0026] The amount of the lubricant added may be adjusted as appropriate, but may be, for example, about 0.001 to 10 mass%, 0.01 to 5 mass%, or even 0.1 to 3 mass% based on the total amount of the lubricant composition. The lubricant composition may contain a plurality of types of molecules (molecules having different carbon numbers (molecular weights), structures (including isomers), etc.) belonging to chemical structural formula (1). The lubricant composition may contain additives other than the lubricant of the present invention. EXAMPLES

[0027] The present invention will be described in more detail with reference to specific examples of lubricants and the like.

[0028] Lubricants (1)Synthesis As shown in Figure 1, oleyl chloride (C 18 H 35 Cl / ) as the starting material, oleylamine bismethyl ester (C 22 H 41 NO4 / R=C 18 H 35 , x=y=1) was synthesized. The details are as follows.

[0029] In a flask (500 ml), add (I) oleyl chloride: 19.37 g (67.5 mmol), (II) dimethyl iminodiacetate hydrochloride (CH 11 NO4+HCl): 15.98 g (81.0 mmol) and dehydrated acetonitrile (CH3CN): 180 ml were added and stirred under an argon atmosphere.

[0030] To this was added 21.63 g (216.0 mmol) of potassium bicarbonate (KHCO3) and 1.12 g (6.75 mmol) of potassium iodide (KI), and the mixture was heated under reflux for 48 hours.

[0031] After cooling the reaction mixture, about 13 ml of acetic acid (C2H4O2) was added to neutralize the reaction mixture, and 200 ml of water was added thereto, followed by extraction twice with 200 ml of ethyl acetate (C4H8O2).

[0032] The obtained organic layer was dried with a drying agent: anhydrous sodium sulfate (Na2SO4). The drying agent was filtered off, and the obtained filtrate was concentrated using an evaporator. The concentrate was purified using a silica gel column (toluene / acetone = 20 / 1 to 10 / 1). In this way, 13.79 g (49.7%) of (III) oleylamine bismethyl ester (simply referred to as the "diester") was obtained as a colorless liquid.

[0033] (2) Structural analysis The synthesized diester 1 The spectrum obtained by H-NMR analysis is shown in Figure 2. Deuterated methanol (CD3OD) was used as the solvent. The analysis was carried out at NARD Laboratory Co., Ltd. using a JEOL Ltd. FT-NMR at a measurement frequency of 400 (399.65) MHz.

[0034] As is clear from the spectra shown in Figure 2, the diester structure of oleylamine (H a , H b , H c ) A characteristic peak was detected.

[0035] "verification" The sliding properties of the synthesized diester were verified by the following wear test.

[0036] (1) Lubricating oil A lubricating oil (lubricating composition) was prepared by blending a diester at a ratio of 0.04 mol / kg with a hydrocarbon base oil (Group III base oil / YUBASE2, SK manufactured by Lubricants) (Sample 1).

[0037] For comparison, lubricating oil (sample C1) containing oleylamine (Sigma-Aldrich O7805) instead of the diester at the same ratio, and lubricating oil (sample C2) containing methyl oleate (Tokyo Chemical Industry Co., Ltd. O0055) at the same ratio were also prepared (sample C1). The amounts added were calculated by mass as sample 1: 1.65 mass%, sample C1: 1.07 mass%, and sample C2: 1.19 mass%.

[0038] (2) Abrasion test A cross-pin wear test, as shown in Figure 3, was conducted using each lubricant (test oil). In the wear test, a rotating pin was pressed against another pin perpendicularly, and pure sliding was performed in a point contact state. Both pins were cylindrical (φ20 mm) made of carburized steel (SCM420), with a surface hardness of 720 to 850 Hv. The pin had a total length of 150 mm, but the central part (length 10 mm) used for analysis was split (replaceable).

[0039] The test conditions are also shown in Figure 3. Specifically, the pressing load between both pins was constant at 20 N (maximum Hertzian surface pressure at the start of the test: approximately 800 MPa). The sliding speed was maintained at 1.2 m / S for 45 minutes, and then decelerated in descending order from 1.0 m / S, 0.7 m / S, 0.5 m / S, 0.3 m / S, 0.2 m / S, and 0.1 m / S. After the deceleration started, each sliding speed was maintained for 3 minutes.

[0040] Each lubricant was heated to a constant temperature of 60°C and supplied to the sliding part at a rate of about 5mL / min using a rotary pump. To confirm reproducibility, the same test was repeated three times for each lubricant. The average values ​​were used to evaluate the sliding characteristics of each lubricant (sample).

[0041] (3) Wear marks An example photograph of the wear mark on the fixed pin after wear tests using each lubricant is shown in Figure 4, along with the wear mark width (average value of three values). The wear mark width is the maximum length in the short direction (longitudinal direction of the rotating pin) formed on the surface of the fixed pin.

[0042] As is clear from Figure 4, Sample 1 had the smallest wear scar and the least surface roughness. The wear scar width of Sample 1 was approximately 41% smaller than that of Sample C1. A comparison of Sample C1 and Sample C2 showed that the presence of an adsorptive group (methyl ester group) at the end of the main chain (oleyl group) improves the sliding properties (wear resistance, adsorptive properties, etc.). Furthermore, a comparison of Sample 1 and Sample C2 showed that the presence of two adsorptive groups (methyl ester groups) at the end rather than one further improves the sliding properties.

[0043] In the case of Sample 1, which had smaller wear scars than the other samples, it is believed that the organic film was stably formed on the sliding surfaces, resulting in excellent sliding properties, even though the substantial pressure acting between the sliding surfaces had increased.

[0044] Incidentally, in the above-mentioned wear test, the sliding speed dependency of the friction coefficient was also evaluated by changing the sliding speed stepwise. Regardless of which sample (lubricant) was used, there was almost no change in the friction coefficient with respect to the sliding speed.

[0045] "supplement" (1) Based on the above results, the influence of the alkyl chain length (x, y in chemical structural formula (1)) of the bisalkyl ester (functional group) was examined by molecular dynamics (MD) using molecular calculation software (Materials Studio / Forcite Plus, manufactured by Dassault Systèmes). Specifically, as shown in Figure 5, the adsorption to the substrate surface was evaluated for mixed oil systems in which oleylamine bismethyl ester (sample 1: x=y=1), oleylamine bispropyl methyl ester (sample 2: x=y=3) and oleylamine (sample C1) were mixed with base oil. Note that oleylamine is a general-purpose friction modifier and is suitable as a standard for adsorption.

[0046] (2) The outline of the calculation method is as follows. First, an FeO(110) surface model was adopted for the substrate surface, assuming a typical oxidation state. In order to accurately reproduce the atomic arrangement and surface charge in the outermost surface area, the FeO(110) surface model reflected structural optimization and charge distribution calculated using an ab initio (first-principles) quantum mechanics calculation tool (CASTEP in Materials Studio) based on density functional theory (DFT). The thickness of the substrate surface was set to six layers of FeO(110) (18.31 Å). Its width was set to a size that would allow two molecules of additive to be arranged side by side (length in the X direction: 49.44 Å, length in the Y direction: 49.53 Å).

[0047] Each additive: 20 molecules and base oil (isodecane: C10H 22 ): A mixed oil model consisting of 180 molecules (density: 0.8 g / cm 3 ) was generated by Amorphous Cell calculations.

[0048] A three-layer model was created by sandwiching each mixed oil model between two FeO(110) planes, one above the other. The three-layer model had a three-dimensional periodic structure with a vacuum layer (20 Å thick) on the top side of the upper FeO(110) plane. Using this model, all atoms on the FeO(110) plane were constrained, and after initial structure optimization calculations using Forcite Plus, molecular dynamics calculations were performed using Forcite Dynamics. The temperature was 373 K (100°C), and the calculation time was 20 ns.

[0049] (3) The initial state and the state after 20 ns obtained for each mixed oil model are shown in FIG. 6A to FIG. 6C (collectively simply referred to as "FIG. 6").

[0050] The adsorption of each additive was evaluated based on the amount of additive (molecules) distributed near the substrate surface after 20 ns. As is clear from Figure 6, Sample 1 and Sample 2 had a higher proportion of additive molecules adsorbed to the substrate surface (sliding surface) than Sample C1.

[0051] Furthermore, the adsorption rate of sample 1 was higher than that of sample 2. In other words, it was found that sample 1 (x=y=1), which has a short alkyl chain length in the functional group (alkyl ester) bonded to oleylamine, has better adsorption properties than sample 2 (x=y=3), which has a long alkyl chain length. This is presumably because sample 1 is less likely to cause steric hindrance in the base oil than sample 2, making it easier to adsorb to the substrate surface.

[0052] Incidentally, when a similar calculation was performed using a Fe2O3(001) surface model for the substrate surface, the order of adsorptivity was the same (same tendency) as when the FeO(110) surface model was used.

Claims

1. A lubricant with the chemical structure shown below. 【Chemistry 1】 (R: a hydrocarbon group having 8 to 24 carbon atoms, x and y: integers of 1 to 6)

2. 2. The lubricant according to claim 1, wherein R is a hydrocarbon group having 18 carbon atoms, and x and y are integers of 1 to 4.

3. Proton nuclear magnetic resonance spectroscopy ( 1 H-NMR) is a chemical shift value of the spectrum, H belonging to the peak group around 3.7 ppm a and, H belonging to the peak group around 2.7 ppm b and, H belonging to the peak group around 5.4 ppm c and, The lubricant of claim 2, which is represented by the following chemical structure: 【Chemistry 2】 (x, y: integers from 1 to 4)

4. A lubricating composition comprising the lubricant according to any one of claims 1 to 3.

5. A sliding machine comprising a sliding surface to which the lubricant according to any one of claims 1 to 3 is supplied.

Citation Information

Patent Citations

  • Lubricating oil composition

    JP2002338983A

  • Lubricant composition

    JP2022024803A